Thickness, Silkiness and Shine of The Hairline of The Offspring of Rams of Different Factory Types - Sattorov Subkhon Bobokulovich; Boymatov Otabek Sabohiddin ugli; Imomov Khurshid Normumin ugli (Genius Publishing Group, 2021)
The article analyzes data on the study of the density, of the silkiness and shine of the hairline of the offspring of rams-producers of various factory types
Keywords: Hair; sura; density; shine